The Existence of The Indigenous People of Passo in The Perspective of Positive Law in Indonesia - Muhammad Satriyo Mandiri; Wilma Silalahi (Eduvest - Journal of Universal Studies, 2024)
The Indonesian state is a state of law as stipulated in Article 1 paragraph (3) of the 1945 Constitution, meaning that as a state of law, all and every action of state administrators and citizens must follow and comply with any applicable regulations or laws. In the concept of a state of law, what is used as the commander in state life is the law itself. As a state of law, Indonesia highly upholds and recognizes the protection of human rights. Protection of human rights means that every citizen and/or community group must be seen as equal. In addition, certain groups that have special needs or vulnerabilities such as indigenous peoples, where the fulfillment of their rights must be treated very extra. This is clearly stated in Article 18B paragraph (2) of the 1945 Constitution. However, empirically, there are rights of indigenous groups that are often violated, such as the indigenous people in Negeri Passo, where their traditional rights in the form of Upulatu or king titles for generations are about to be revoked by parties who are supposed to protect and guarantee their customary legal rights. However, in reality, they actually tried to take away the traditional rights of the indigenous people in Negeri Passo by making new local regulations using their power/office, which resulted in losses to the indigenous people themselves. As a result, these indigenous groups find it difficult to obtain legal certainty as indigenous peoples.